0D Cs3Cu2X5 (X = I, Br, and Cl) Nanocrystals: Colloidal Syntheses and Optical Properties. Issue 3 (13th December 2019) - Luo, Zhishan; Li, Qian; Zhang, Liming; Wu, Xiaotong; Tan, Li; Zou, Chao; Liu, Yejing; Quan, Zewei
Abstract: 0D lead‐free metal halide nanocrystals (NCs) are an emerging class of materials with intriguing optical properties. Herein, colloidal synthetic routes are presented for the production of 0D Cs3 Cu2 X5 (X = I, Br, and Cl) NCs with orthorhombic structure and well‐defined morphologies. All these Cs3 Cu2 X5 NCs exhibit broadband blue‐green photoluminescence (PL) emissions in the range of 445–527 nm with large Stokes shifts, which are attributed to their intrinsic self‐trapped exciton (STE) emission characteristics. The high PL quantum yield of 48.7% is obtained from Cs3 Cu2 Cl5 NCs, while Cs3 Cu2 I5 NCs exhibit considerable air stability over 45 days. Intriguingly, as X is changed from I to Br and Cl, Cs3 Cu2 X5 NCs exhibit a continuous redshift of emission peaks, which is contrary to the blueshift in CsPbX3 perovskite NCs. Abstract : 0D all‐inorganic Cs3 Cu2 X5 (X = I, Br, and Cl) nanocrystals (NCs) with orthorhombic structure and well‐defined morphologies are produced. The NCs exhibit a continuous redshift of broadband blue‐green photoluminescence emissions in the range of 445–527 nm as X is changed from I to Br and Cl, which are attributed to their intrinsic self‐trapped exciton emission characteristics.